Role of salicylic acid pre-treatment on the photosynthetic performance of tomato plants (Lycopersicon esculentum Mill. L. cvar. Rio Fuego) under salt stress - Gémes, Katalin (Acta Biologica Szegediensis, 2008)
Imposition of salt stress reduced the net CO2 assimilation rate, chlorophyll (Chl), anthocyanin and carotenoid contents, stomatal conductance and soluble sugar contents of tomato (Lycopersicon esculentum Mill. L. cv. Rio Fuego). Pre-treatments of plant with 10-4 M salicylic acid (SA) could partially restore the CO2 fixation rate and photosynthetic pigment levels under 100 mM NaCl exposure. Accumulation of soluble sugars, a biochemical marker of salinity tolerance in tomato, could be detected in pre-treated plants exposed to high salinity. The improved photosynthetic performance, the accumulation of soluble sugars as compatible osmolytes contributed to the successful acclimation of 10-4 M SA pre-treated tomato plants to salt stress.